Integrated Geochemical Approaches for Water Remediation in the Golden Triangle, Egypt - Hassan, Tharwat Mohamed Salem (2023)
Egypt Vision 2030 is centred on a number of national initiatives, including the Golden Triangle Economic zone, the Siemens-Egypt project, the New Suez Canal project, the El-Dabaa power plant, and the New Administrative City. As a consequence, the Egyptian economy will become more competitive on a worldwide scale. The second national mega project, the Golden Triangle Economic zone, is situated in the Eastern Desert stretched between the towns of Qena, Safaga, and Qusir, and it aspires to create a new industrial capital in this attractive region. The Eastern Desert in general and the Golden Triangle in particular are now seeing a renaissance of mining and exploration activity. The initiative intends to create a new economic activity based on the available natural resources and their prime position between the Nile Valley and the Red Sea. Growing the agricultural land in the Nile Valley, establishing new industries and desalination plants, creating new urban settlements, expanding the mining operations, exploiting certain mineral reserves, and creating new resorts and tourist villages are some of the potential development activities. The quality and accessibility of water resources are crucial for achieving these prospective goals. Heavy metal species and concentrations in the groundwater of the Golden Triangle area of Egypt have been assessed. In particular, the thesis demonstrates the degree of groundwater contamination with heavy metals in the study area, taking into consideration the role of geogenic and anthropogenic activities. Moreover, a novel geopolymer adsorbent was successfully synthesized from a heterogeneous natural aluminosilicate precursor for metal ions sequestration. Heavy metal concentrations and species were determined based on the multielement chemical analysis of the groundwater samples. The calculated HPI index revealed that the groundwater in the Golden Triangle area is contaminated with serious heavy metals. The contamination level is in the order of coastal zone>crystalline rocks zone>Nile valley zone. The groundwater samples HW, BH and FKH are not suitable for drinking purposes due to the presence of high levels of toxic metal ions such as As, Mn, Cd, Co, Ni, Se, V, and Tl. The geopolymerization of a heterogeneous geological precursor, calcareous red mudstone, was investigated. The experimental and analytical techniques confirmed an improved reactivity with increasing the thermal activation up to 800 ⁰C. Moreover, feeding the geopolymer slurry with a more silicate was necessary during the geopolymerization process to reduce the effect of carbonation and to ensure a well-developed structure. The alkali activation of mudstone resulted in the formation of various hydration products, including calcium aluminium silicate hydrate, sodium aluminium silicate hydrate and sodium ferrosialate hydrate phases. The calcareous red mudstone geopolymer adsorbents demonstrated improved adsorption removal in comparison to the raw material. Cd2+, Co2+, Ni2+, and Mn2+ sequestration on the geopolymer surfaces was hypothesised to occur by the ion exchange, surface complexation and electrostatic interaction mechanisms. The effectiveness of the metal ions removal from groundwater, a highly competitive system, has been examined. The statistical regression analysis showed that the data best fit with the Langmuir adsorption rather than the Freundlich isotherm. Additionally, the interaction between the geopolymer adsorbent and metal ions could be described by a pseudo-second-order kinetic model. Thermodynamics suggested an endothermic, spontaneous, and chemical adsorption mechanism.